2019
DOI: 10.1016/s1470-2045(18)30828-3
|View full text |Cite
|
Sign up to set email alerts
|

New therapeutic perspectives to manage refractory immune checkpoint-related toxicities

Abstract: Immune-checkpoint inhibitors (ICIs) are reshaping the prognosis of many cancer types and are progressively becoming a standard of care for many of them. Cancer immunotherapy has started a revolution in the oncology therapeutic landscape, bringing new hope to patients but also a whole new spectrum of toxicities for practitioners to manage. Oncologists and specialists involved in the pluridisciplinary management of immune-related adverse events (irAEs) are increasingly confronted with the therapeutic challenge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
153
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(168 citation statements)
references
References 82 publications
(69 reference statements)
3
153
0
2
Order By: Relevance
“…A retrospective series that included 298 patients who received ipilimumab for melanoma found that 35% of patients required steroids for an irAE and 10% of patients required additional systemic immunosuppression, highlighting the importance of optimizing treatment algorithms for patients with refractory irAEs. Data to inform the management of refractory irAEs are often drawn from case reports, small series, and expert opinions given a lack of prospective data . A recent review of emerging strategies to manage refractory irAEs suggests that biologic therapy for refractory irAEs could be selected based on the pathophysiology of the specific irAE .…”
Section: Checkpoint Inhibitorsmentioning
confidence: 99%
See 3 more Smart Citations
“…A retrospective series that included 298 patients who received ipilimumab for melanoma found that 35% of patients required steroids for an irAE and 10% of patients required additional systemic immunosuppression, highlighting the importance of optimizing treatment algorithms for patients with refractory irAEs. Data to inform the management of refractory irAEs are often drawn from case reports, small series, and expert opinions given a lack of prospective data . A recent review of emerging strategies to manage refractory irAEs suggests that biologic therapy for refractory irAEs could be selected based on the pathophysiology of the specific irAE .…”
Section: Checkpoint Inhibitorsmentioning
confidence: 99%
“…The most common irAEs treated with tocilizumab were pneumonitis and serum sickness/systemic inflammatory response syndrome, and clinical improvement was observed in 27 of 34 patients. IL‐6 expression has been shown to promote tumor growth and metastasis; therefore, IL‐6 blockade may offer the potential for the effective treatment of refractory irAEs and maintenance of immunotherapy efficacy …”
Section: Checkpoint Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, CTLA‐4 blockade seems to increase the availability of ligands for CD28 permitting the activation of potentially self‐reactive T cells . This hypothesis leads to a series of therapeutic proposals in severe steroid‐resistant irAEs . Furthermore, the role of infectious agents has been proposed, suggesting a similarity with immune reconstitution syndrome in human immunodeficiency virus (HIV) and pathogen‐induced immune response .…”
Section: Physiopathological Mechanismsmentioning
confidence: 99%